Investigation Extraction of the Garden Snail's Shells using GC-MS Spectrometry - Kadhim, Abdulrazzaq B; Almhanna, Hazem (Journal La Lifesci, 2022)
This study focused on the powder of the shell of the local garden snail in Iraq to identify the chemical compounds and determine the diversity and biological contents that might be applied for other applications and studies. Thus, snails shell was collected from local rivers in Al Diwaniya city, middle of Iraq; 500 grams of the shell powder of the garden snail was smashed and grinded and analysed during this study. The shell powder was extracted by ethanol, and 250mg of the yield was injected in GC-Mass spectrometry and analyzed. The detection of chemical compounds in the garden snail shell was identified by comparison with the mass spectra library of the GC-Mass data system. Results exhibited that six chemical compounds were largely predominant among other elements of the shell powder, including hexadecanoic acid, ethyl ester, (E)-9-Octadecenoic acid ethyl ester, pentadecanoic acid, heptadecanoic acid, ethyl ester, and 9-Octadecenamide, (Z)-. Also, the analysis profiled more than 23 chemical compounds that constituted the structure of the garden snail shell with a low percentage area. These substances were classified into fatty acids, saturated fatty acids, organic compounds, natural products, and methyl and ethyl esters. Consequently, these natural materials are essential active compounds that could be used for more medical and research applications studies. However, the yield of chemical compounds was a low amount. To sum up, GC-Mass spectrometry has displayed a high biological diversity of chemical compounds substances in the shell of garden snails, which can help researchers to investigate more for different natural chemical resources in the shell of a garden snail.